Avaliação dos níveis de radiação não ionizante em ambientes de trabalho de uma universidade brasileira - Silva, Sonaly de Lima (2018)
Non-ionizing radiation (NIR) is a type of electromagnetic radiation present in the most various types of environments, originating from diverse sources such as computers, printers, notebooks, telephones, power networks, electric power transformers, microwaves, and other consumer electronics. Despite not generating ionization, this type of radiation raises concerns regarding the exposure of employees in work environments with electronic equipment.The International Agency for Research on Cancer stated in a report from 2002 that exposure to electromagnetic radiation is possibly carcinogenic to humans. Several studies have been performed to identify the correlation between the human exposure to NIR and the development of several pathologies. Thus, work environments with electronic equipment may expose their employees to health problems. Therefore, this research presents an evaluation of the NIR levels in working environments with visual display terminals (VDT) and other electronic resources. Four rooms were selected from a public University - two department offices, a study laboratory and a computer room - all with different internal characteristics including the number of devices and employees, layout, area and location. The magnetic flux density was mapped in the work environment. Different points in the environment, spaced 1meter apart, were selected for measurement in six frequency band intervals: 1-8Hz, 8-25Hz, 25-50Hz, 50 -400Hz, 400-3kHz, 3 kHz-30 kHz. Graphical descriptive analyses of the magnetic flux density found in each environment were developed, and the oscillation in each frequency band interval was determined. Another analysis regarding the magnetic flux density, especially for the data measured near the employees, aimed to represent the density levels over time by means of a probability distribution. Simultaneously, both the profiles and reports of complaints of the employees who performing their activities in these rooms were obtained through surveys addressing questions regarding their professional life, characteristics of their work activities, physical activity, habits, and perceived symptoms throughout and after their workday. The data obtained from this questionnaire were summarized and a descriptive analysis of these data was performed to identify the employees working in the environments studied. To identify possible health damages to the employees, which would be indicated by heating of the skin, thermal images of an employee were obtained. These images were analyzed with the aid of Matlab software for quantitative verification of skin temperature increase, presented in the images. It was verified that the environments that have different internal characteristics present magnetic flux densities that vary according to the (1) positioning, the type and quantity of the NIR sources internal to the environment; o (2) layout and distribution of these sources in the environment; and (3) external factors, such as the presence of electric power frames. Reports of daytime drowsiness and difficulty getting out of bed were more frequent. From the thermal mapping that allowed to evaluate the induction of magnetic field generated in the body of the was verified low relation between the thermal variation and the magnetic flux density.